Enhanced bone regeneration in rat calvarial defects implanted with surface-modified and BMP-loaded bioactive glass (13-93) scaffolds - Liu, Xin (2013)
The repair of large bone defects, such as segmental defects in the long bones of the limbs, is a challenging clinical problem. Our recent work has shown the ability to create porous scaffolds of silicate 13-93 bioactive glass by robocasting which have compressive strengths comparable to human cortical bone. The objective of this study was to evaluate the capacity of those strong porous scaffolds with a grid-like microstructure (porosity = 50%; filament width = 330 μm; pore width = 300 μm) to regenerate bone in a rat calvarial defect model. Six weeks postimplantation, the amount of new bone formed within the implants was evaluated using histomorphometric analysis. The amount of new bone formed in implants composed of the as-fabricated scaffolds was 32% of the available pore space (area). Pretreating the as-fabricated scaffolds in an aqueous phosphate solution for 1, 3, and 6 days, to convert a surface layer to hydroxyapatite prior to implantation, enhanced new bone formation to 46%, 57%, and 45%, respectively. New bone formation in scaffolds pretreated for 1, 3, and 6 days and loaded with bone morphogenetic protein-2 (BMP-2) (1 μg/defect) was 65%, 61%, and 64%, respectively. The results show that converting a surface layer of the glass to hydroxyapatite or loading the surface-treated scaffolds with BMP-2 can significantly improve the capacity of 13-93 bioactive glass scaffolds to regenerate bone in an osseous defect. Based on their mechanical properties evaluated previously and their capacity to regenerate bone found in this study, these 13-93 bioactive glass scaffolds, pretreated or loaded with BMP-2, are promising in structural bone repair.